2017
DOI: 10.1259/bjr.20160834
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post-contrast 3D-T1-MPRAGE, 3D-T1-SPACE and 3D-T2-FLAIR MR images in evaluation of meningeal abnormalities at 3-T MRI

Abstract: The 3D-T-SPACE sequence best demonstrated abnormalities in dural and sulcal spaces, whereas FLAIR was useful for abnormalities in basal cisterns. Both SPACE and FLAIR performed holds good for detection of gyral enhancement. Post-contrast SPACE and FLAIR sequences are superior to the MPRAGE sequence for evaluation of meningeal abnormalities and when used in combination have the maximum sensitivity for leptomeningeal abnormalities. The negative-predictive value is nearly 100%, where no leptomeningeal abnormality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…[910] 3D SPACE sequence also plays a role in communicating hydrocephalus as in tuberculous meningitis, which is very common in developing countries such as India, by detecting the altered signal intensity to loss of signal intensity in the basal cisterns by inflammatory cells. [11] It is a modification of 3D turbo spin echo sequence where the whole imaging volume is excited so that the images can be reconstructed in multiple planes. It uses radiofrequency pulses with variable flip angles, which are nonselective, short refocusing pulse trains with very high turbo factors, and high sampling efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[910] 3D SPACE sequence also plays a role in communicating hydrocephalus as in tuberculous meningitis, which is very common in developing countries such as India, by detecting the altered signal intensity to loss of signal intensity in the basal cisterns by inflammatory cells. [11] It is a modification of 3D turbo spin echo sequence where the whole imaging volume is excited so that the images can be reconstructed in multiple planes. It uses radiofrequency pulses with variable flip angles, which are nonselective, short refocusing pulse trains with very high turbo factors, and high sampling efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interval between IR pulses must be sufficiently long (e.g., 1 ~ 4 s) to allow for the recovery of longitudinal magnetization to maintain decent SNR. This often leads to long scanning times, especially for 3D imaging, even with advanced acceleration strategies and high readout bandwidths 10,17 …”
Section: Discussionmentioning
confidence: 99%
“…The other is using gradient echo (GRE) acquisition, with the combination of short repetition times (TR), high excitation flip angles (FAs), and signal‐spoiling mechanisms, 7,8 to create the incoherent steady state (ISS) signals that are also T 1 weighted. Generally speaking, IR‐based methods 9–11 can offer stronger T 1 contrasts than SR and steady state methods.…”
Section: Introductionmentioning
confidence: 99%
“…Another study was done by Jeevanandham et al . [22] on 78 patients with suspicion of meningeal abnormalities. They observed that 3D T1-SPACE was useful in detecting meningeal abnormalities along sulci whereas 3D T2-FLAIR was useful in detecting meningeal abnormalities along basal cisterns.…”
Section: Discussionmentioning
confidence: 99%